2020
DOI: 10.1177/1354068820908021
|View full text |Cite
|
Sign up to set email alerts
|

Does policy motivation drive party activism? A study of party activists in three Asian democracies

Abstract: Studies of party activism highlight that party activists are driven by various motivations and that these affect their level of activism. However, it remains unclear whether policy-motivated activists are more engaged in party activities than those motivated by other incentives and whether the motivation–activism link varies with party characteristics. This article investigates these questions by focusing on political actors linking parties and voters in the local community. I use a party activist survey data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(37 reference statements)
0
2
0
1
Order By: Relevance
“…It also makes sense that the dissatisfaction might be greater for the party members who never benefitted from the incentives the party has to offer-in the form of mandates or board positions-than for those who have, therefore establishing a relationship between ideological preferences and objective social positions. Koo (2021) as well as Caletal et al (2013) found that one's position in the party is related to their confidence and general satisfaction with the party processes. Nevertheless, not everyone dissatisfied with the inclusion level of members supports the introduction of online consultations: a certain level of mistrust toward digitalization might still be associated even in this group, which needs to be further researched to properly explain.…”
Section: Discussion and Summarymentioning
confidence: 96%
“…It also makes sense that the dissatisfaction might be greater for the party members who never benefitted from the incentives the party has to offer-in the form of mandates or board positions-than for those who have, therefore establishing a relationship between ideological preferences and objective social positions. Koo (2021) as well as Caletal et al (2013) found that one's position in the party is related to their confidence and general satisfaction with the party processes. Nevertheless, not everyone dissatisfied with the inclusion level of members supports the introduction of online consultations: a certain level of mistrust toward digitalization might still be associated even in this group, which needs to be further researched to properly explain.…”
Section: Discussion and Summarymentioning
confidence: 96%
“…These writers stress that the 2016 American presidential election figures such as Bill Clinton used slogans Like "I am with her" in his campaign to appeal to and motivate supporters. While Koo (2021) linked political activism to party membership and policy. He argued that election-related activities were driven by these two factors.…”
mentioning
confidence: 99%
“…Über die Motivation für die Mitgliedschaft in einer Partei ist bereits einiges bekannt. So spielen dort sozialpsychologische Aspekte, wie auch generelle Nutzenerwägungen eine Rolle (Hoffmann 2011;Seyd und Whiteley 1992;Koo 2021;Gomez et al 2019;Achury et al 2020). Diesen Untersuchungen ist jedoch gemein, dass sie in der Regel durch die Betrachtung der etablierten Parteien oder der Parteimitgliedschaft im Aggregat nur einen Ausschnitt der Parteienlandschaft und seiner Mitglieder abbilden oder sehr unterschiedliche Parteien in einer Gesamtschau betrachten.…”
unclassified